How to do research methodology: From Literature Review, Bibliometric, Step-by-step Research Stages, to Practical Examples in Science and Engineering Education (Indonesian Journal of Science and Technology, 2025)
This paper explains how to do research in science and engineering education. To support the explanation, the paper was supported by a literature review for research design and computational bibliometric analysis. We mapped several types of research methodologies, supported by several examples from researchers and practitioners who were involved in these research topics. We also developed 9 steps in research methodology, namely PHMEEDERID, an abbreviation of Identify Problems; Develop Hypothesis; Choose Research Methodology; Conduct Experiments and Create Equipment; Refine Design and Develop; Evaluate and Test; Do Revision and Retest; Implement; and Disseminate. The step-by-step method was also added to make readers and users easily understand. This study has the potential to be used as standard information for scientists, teachers, educators, and practitioners in doing research in science education and engineering education.
Keywords: Chemical Engineering; Engineering Education; Research Methodology; Science Education; Vocational